Adobe after effects 4.0: user guide windows and macintosh - Adobe Systems Incorporated and its licensors (Adobe systems incorporated: s/e, 1998)
Contents: 1. getting started. 2. a quick tour of adobe after effects. 3. working with projects, windows, and palettes. 4. preparing and importing footage. building a composition. managing layers. animating layers. 5. fine-tuning animation. 6. working with masks and tranparency. 7. applying effects. 8. managing projectts effectively. 9. rendesing a movie
Keywords: Informática - Guide for Windows